2019
DOI: 10.30831/akukeg.335187
|View full text |Cite
|
Sign up to set email alerts
|

Matematik Öğretmeni Adaylarının Ölçme ve Değerlendirme Bilgi Gelişimleri

Abstract: The purpose of the study was to investigate assessment knowledge developments of prospective mathematics teachers during the undergraduate education. The explanatory-confirmatory research design, one of the mixed research designs, was used in this study. The participants of the study consist of 176 prospective teachers in total, 44 of them being first-grade, 44 second-grade, 44 third-grade, and 44 fourth-grade students studying at the department of elementary school mathematics education of a university in Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
1
0
4
Order By: Relevance
“…The implementation of the new curriculum showed that the teachers lack knowledge regarding alternative assessment and evaluation tools proposed for mathematics course, they adopt these assessment tools, yet they cannot make a decent use of them; and the students find it difficult to understand the purpose of alternative assessment and evaluation tools (Peker and Gülle, 2011). Previous studies show that these assessment approaches that are re-created in mathematics teaching departments are not adequately employed by pre-service mathematics teachers (Şahin and Soylu, 2019;Toptaş, 2011) and mathematics teachers (Arıbaş and Göktaş, 2014;Bal and Doğanay, 2010;Birgin and Baki, 2012;Cansız Aktaş and Baki, 2013;Duru and Korkmaz, 2010;Gelbal and Kelecioğlu, 2007;Karakuş, 2010;Karakuş and Yeşilpınar, 2013;Önel anothers, 2020;Tuncel and Kazu, 2019) in terms of carrying out alternative assessments. The use of technology in education is more and more in demand and considered a need in assessment terms in addition to teaching and learning dimensions (Işık, Çukurbaşı, Fidan, Debbağ, and Erkan, 2017).…”
Section: Extended Abstract Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of the new curriculum showed that the teachers lack knowledge regarding alternative assessment and evaluation tools proposed for mathematics course, they adopt these assessment tools, yet they cannot make a decent use of them; and the students find it difficult to understand the purpose of alternative assessment and evaluation tools (Peker and Gülle, 2011). Previous studies show that these assessment approaches that are re-created in mathematics teaching departments are not adequately employed by pre-service mathematics teachers (Şahin and Soylu, 2019;Toptaş, 2011) and mathematics teachers (Arıbaş and Göktaş, 2014;Bal and Doğanay, 2010;Birgin and Baki, 2012;Cansız Aktaş and Baki, 2013;Duru and Korkmaz, 2010;Gelbal and Kelecioğlu, 2007;Karakuş, 2010;Karakuş and Yeşilpınar, 2013;Önel anothers, 2020;Tuncel and Kazu, 2019) in terms of carrying out alternative assessments. The use of technology in education is more and more in demand and considered a need in assessment terms in addition to teaching and learning dimensions (Işık, Çukurbaşı, Fidan, Debbağ, and Erkan, 2017).…”
Section: Extended Abstract Introductionmentioning
confidence: 99%
“…Millî Eğitim Bakanlığı (MEB, 2017) yayınladığı genelgede, öğretmenlerin alanına ve öğrencilerin gelişimsel özelliklerine uygun ölçme ve değerlendirme araçları hazırlayıp kullanabilmeleri böylece süreç ve sonuç temalı dersler vurgusunu yapmıştır. Bundan dolayı, öğretmenler ve öğretmen adayları ölçme değerlendirmenin sadece not verme amaçlı değil aynı zamanda öğrencinin gelişiminin ve öğrenme sürecinin değerlendirilmesi amacıyla yapıldığının farkında olmalıdırlar (Şahin & Soylu, 2019). Sürece ağırlık verilmesi ve öğrenci performanslarının her yönden değerlendirilmesinin hedeflenmesi nedeniyle ölçme ve değerlendirme araçlarının çeşitliliği artmaktadır (Gelbal & Kelecioğlu, 2007).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Bu süreçte öğretmen adaylarının öğrencilere rehberlik edebilecek bilgi ve beceri ile mezun olmuş olmaları için hizmetöncesinde aldıkları eğitim sürecinde birçok farklı değerlendirme durumu ile karşı karşıya gelmeleri sağlanmalıdır (Nalbantoğlu Yılmaz, 2017). Nitekim alanyazındaki çalışmalarda öğretmen adaylarının alternatif ölçme-değerlendirme yöntemlerinin kullanılmasında sorunlar yaşadığı görülmekte ve öğretmen adaylarının ölçmedeğerlendirme alanına yönelik bilgi ve becerilerinin gelişmesi için uygulamalara önem verilmesi gerektiği vurgulanmaktadır (Beydoğan, 2017;Darling-Hammond ve Baratz-Snowden, 2007;Karaman ve Şahin, 2014;Şahin ve Soylu, 2019). Belirtilen tespitlerden hareketle, bu araştırmada mikroöğretim ile öz, akran, grup ve öğretim üyesi değerlendirme (ÖAGÖD) uygulamalarının ilköğretim matematik öğretmen adaylarının mesleki yeterlik ve yeterlik inançlarının üzerindeki etkisini incelemek ve uygulama süreci ile kullanılan değerlendirme yöntemlerine yönelik görüşlerini belirlemek amaçlanmıştır.…”
Section: Introductionunclassified
“…Çalışmalarda çoğunlukla ölçme ve değerlendirme konusunda yeterliklerin belirlenmesine odaklanılmış, subjektif bilgilere ulaşılmıştır (Bütüner, Yiğit ve Çimer, 2010). Öte yandan değerlendirme okuryazarlığı ile ilgili çalışmalarda ise öğretmen adaylarının (Beziat ve Coleman, 2015;Ogan-Bekiroğlu ve Suzuk, 2014;Efendi, Rustaman ve Kaniawati, 2017;Karaman, 2014;Şahin ve Soylu, 2019;Volante ve Fazio, 2007;Yalvaç, 2016) ve öğretmenlerin (Büyükkarcı, 2016;Kanjee ve Mthembu, 2015;Mede ve Atay, 2017;Tao, 2014;Xu ve Brown, 2017) değerlendirme okuryazarlığının düşük olduğu ya da yeterli seviyede olmadığı ortaya çıkmıştır. Öğretmen adayları (Gebril, 2017;Mertler, 2003Mertler, , 2004 ile öğretmenlerin (Gebril, 2017;Mertler, 2003Mertler, , 2004Pfeiffer-Hoens, 2017;Plake, 1993) değerlendirme okuryazarlık düzeyinin orta düzeyde olduğunu ortaya koyan çalışmalar da mevcuttur.…”
Section: Introductionunclassified